1992
DOI: 10.1007/bf02098083
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia in childhood: Etiology and response to antimicrobial therapy

Abstract: A prospective eight-month study was carried out in 50 children admitted to hospital for radiologically confirmed community-acquired pneumonia. A potential causative agent of infection was identified in 44 (88%) cases. Using virus isolation, virus antigen detection and enzyme immunoassay serology, respiratory virus infection was diagnosed in 30 (60%) patients. Antibody assays for seven bacteria and antigen detection from serum and urine for Streptococcus pneumoniae produced evidence of bacterial infection in 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0
17

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 34 publications
8
37
0
17
Order By: Relevance
“…These results may corroborate previously reported etiological rates; in previous studies, the rate has been reported as 43% to 85% (14)(15)(16)(17)(18)(19)(20).…”
Section: Resultssupporting
confidence: 93%
“…These results may corroborate previously reported etiological rates; in previous studies, the rate has been reported as 43% to 85% (14)(15)(16)(17)(18)(19)(20).…”
Section: Resultssupporting
confidence: 93%
“…pneumoniae causes up to 40% or more of cases of community-acquired pneumonias and as many as 18% of cases requiring hospitalization in children (5,47,137,156,180,182,199,273,357,403,446). Older studies relying upon serology and culture reported M. pneumoniae pneumonia to be somewhat uncommon in children aged less than 5 years and greatest among school-aged children 5 to 15 years of age, with a decline after adolescence and on into adulthood (5,(143)(144)(145).…”
Section: Demographics and Spectrum Of Diseasementioning
confidence: 99%
“…Mycoplasma pneumoniae is a common aetio-logical agent of community-acquired pneumonia in both children and adults 1,2 . It can cause a wide variety of respiratory tract manifestations including acute pharyngitis, bronchitis, bronchiolitis and bronchopneumonia.…”
Section: Introductionmentioning
confidence: 99%